Legal Protection for Creditors Holding Fiduciary Guarantee Due to Debtor Default: Perlindungan Hukum Bagi Kreditur Pemegang Jaminan Fidusia Akibat Debitur Wanprestasi - Andari, Chyci Hesty; Mediawati, Noor Fatimah (Indonesian Journal of Law and Economics Review, 2021)
This study aims to determine the form of legal protection for creditors holding fiduciary guarantees due to default debtors at PT Batavia Prosperindo Finance, Tbk Sidoarjo Branch. This type of research includes juridical-normative research, with a chase approach (case approach), primary legal materials. Civil Law/Burgelijk Wetboek and Article 33 of the 1945 Constitution and Letter of Credit Agreement from PT Batavia Prosperindo Finance, Tbk Sidoarjo Branch, deductive data analysis. The results of this study indicate that legal protection for creditors who hold fiduciary guarantees due to debtors who default (a case study at PT Batavia Prosperindo Finance, Tbk Sidoarjo Branch that preventive and familial legal protection is prioritized by PT Batavia Prosperindo Finance in the form of demanding the debtor for the fulfillment of performance only , fulfillment of achievements accompanied by compensation (Article 1267 of the Civil Code), demanding and asking for compensation (only possible losses due to delays, cancellation of agreements, cancellations accompanied by compensation. Settlement of debtor defaults can be done through litigation by reporting to the authorities and also through other channels). Non Litigation, namely negotiations with the debtor.